Activated carbon for capturing carbon dioxide as well as preparation method and application of activated carbon

By using sludge and oil-based paint as raw materials, combined with free radical polymerization, carbonization and activation, the problems of high preparation cost of activated carbon and low CO2 adsorption efficiency in the prior art are solved, and efficient and low-cost CO2 adsorption are achieved. Effect.

CN119430179APending Publication Date: 2025-02-14ZHEJIANG UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411330146.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing activated carbon preparation methods have limitations on raw materials, high production costs, high equipment and technical requirements, making it difficult to effectively capture and utilize carbon dioxide.

Method used

Sludge and oil-based paint are used as raw materials to prepare activated carbon through free radical polymerization, carbonization and activation steps, and combined with the reaction activation and modification of KOH and H2SO4 to form an efficient CO2 adsorbent.

Benefits of technology

The prepared activated carbon has low cost, excellent CO2 adsorption selectivity and high adsorption capacity, which can reach 3.3 times the CO2 adsorption amount of conventional activated carbon, solves the problems of sludge treatment and resource utilization, and has significant environmental and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention discloses activated carbon for capturing carbon dioxide and a preparation method and application thereof.The preparation method of the activated carbon comprises the steps that waste sludge is dried to constant weight, smashed and sieved to obtain sludge powder, under the protection of inert atmosphere, the sludge powder, oil paint and an initiator azodiisobutyronitrile are heated and stirred in ethyl alcohol, a free radical polymerization reaction is conducted, and the activated carbon is obtained; the preparation method comprises the following steps: precipitating a solid in the process, filtering, drying, preparing oily paint sludge, carbonizing at high temperature in a tubular furnace in which N2 atmosphere is introduced, immersing the obtained carbon material in a KOH aqueous solution, heating, stirring and reacting, after the reaction is finished, carrying out suction filtration and drying, and calcining and activating the dried sample in the tubular furnace in which N2 atmosphere is introduced, thereby obtaining the oily paint sludge. And immersing the activated sample in a sulfuric acid solution, heating and stirring for reaction, and after the reaction is finished, performing suction filtration and drying to obtain the activated carbon product. The activated carbon prepared by the invention has the advantages of low cost, good adsorption selectivity and large CO2 adsorption capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of waste gas treatment, and in particular to activated carbon for capturing carbon dioxide, and a preparation method and application thereof. Background Art

[0002] Carbon dioxide (CO2) is a colorless, odorless gas and one of the main contributors to the greenhouse effect. Its accumulation in the atmosphere leads to global warming, triggers extreme weather events, and has a profound impact on ecosystems and human society. CO2 mainly comes from activities such as the burning of fossil fuels, industrial production, and deforestation. Therefore, if CO2 can be effectively captured and utilized, it will not only reduce greenhouse gas emissions and protect air quality, but also realize the resource utilization of CO2 and reduce the energy consumption caused by the production of CO2.

[0003] Sludge produced by urban sewage treatment plants contains a variety of potentially toxic and harmful components, such as pathogenic bacteria, heavy metals and organic pollutants. Untreated sewage plant sludge can cause serious pollution to groundwater, surface water and soil. Using sludge as raw material to prepare activated carbon can effectively reduce carbon emissions, produce sustainable adsorbents, reduce land occupation and environmental pollution, and has good application prospects in the utilization of sludge resources. In addition, using sludge as raw material has the advantage of low cost. Sludge is almost a free resource. Using sludge as raw material can significantly reduce production costs.

[0004] Conventional activated carbon preparation methods mainly include physical activation, chemical activation, physical-chemical activation, etc., but there are still many disadvantages, such as raw material restrictions. The supply of high-quality activated carbon production raw materials such as clean coal and fruit shells is becoming increasingly tight, which directly affects the production cost and output of activated carbon. With the improvement of environmental protection requirements, the restrictions on the use of wood are more stringent, resulting in challenges for traditional charcoal preparation methods; the preparation cost is too high. Although the new preparation method is more environmentally friendly, the equipment and technology required are relatively high-end, and the initial investment is large, which is a considerable burden for small enterprises and emerging markets.

[0005] Adsorption is a technique that uses porous materials to adsorb gases. This method is mainly based on the characteristics of porous materials and their selectivity for adsorption of specific gases. It can intercept, accumulate or concentrate certain components in the mixed gas on the surface of the adsorbent. In this way, the adsorption method can effectively separate different components in the mixed gas. Using sludge-based activated carbon as an adsorbent can effectively capture CO2 gas. The CO2 adsorption capacity of the activated carbon prepared by the present invention can reach 3.3 times that of conventional activated carbon. Summary of the invention

[0006] In view of the above-mentioned technical problems existing in the prior art, the purpose of the present application is to provide an activated carbon for capturing carbon dioxide and a preparation method and application thereof. The activated carbon prepared in the present application has the advantages of low cost, good adsorption selectivity and large adsorption capacity for CO2.

[0007] The technical solution adopted by the present invention is as follows:

[0008] An activated carbon for capturing carbon dioxide and a preparation method and application thereof, comprising the following steps:

[0009] 1) Waste sludge from a sewage treatment plant is used as a raw material, first dried in an oven to constant weight, then crushed and sieved to obtain sludge powder; then, under the protection of an inert atmosphere, the sludge powder, oily paint, and an initiator azobisisobutyronitrile are heated and stirred in ethanol to carry out a free radical polymerization reaction, solids are precipitated in the process, filtered, and dried to obtain oily paint sludge;

[0010] 2) Carbonizing the oily paint sludge at high temperature in a tubular furnace with N2 atmosphere to obtain carbon material;

[0011] 3) The carbon material is immersed in a KOH aqueous solution and heated and stirred for reaction. After the reaction is completed, the carbon material is filtered and dried. The dried sample is then placed in a tubular furnace with a N2 atmosphere for calcination and activation;

[0012] 4) immersing the sample activated in step 3) in a sulfuric acid solution, heating and stirring to react, and after the reaction is completed, filtering and drying to obtain the activated carbon product.

[0013] Furthermore, in step 1), the water content of the waste sludge is 55%-60%, and the rest is mainly organic matter and ash, and the organic matter content is 40%-50% of the total content of organic matter and ash; the oil-based paint is a UV paint with a polyester content of more than 50%.

[0014] Furthermore, in step 1), the solid-liquid ratio of sludge powder to oil-based paint is 1:1-3, preferably 1:1.5-2; the amount of azobisisobutyronitrile is 0.5-2% of the mass of the oil-based paint, preferably 0.8-1%; the volume ratio of the oil-based paint to ethanol is 1:0.5-2, preferably 1:0.8-1.

[0015] Furthermore, the temperature of the free radical polymerization reaction in step 1) is 60°C ± 5°C, and the reaction time is 20-30h. The principle of the free radical polymerization reaction of the present invention is as follows:

[0016] 1. Generation of free radicals, decomposition of azobisisobutyronitrile (AIBN). AIBN decomposes at around 60°C to generate free radicals, which can initiate subsequent polymerization reactions.

[0017] AIBN→2C4H6N2+2·CH3

[0018] 2. Oil-based paints usually contain unsaturated double bonds (such as vinyl, acrylate, etc.). The generated free radicals attack the double bonds in the oil-based paint, triggering a chain growth reaction. The generated new free radicals continue to attack other double bonds to form longer polymer chains.

[0019] ·CH3+R-CH=CH-COOH→R-CH-CH-COOH·

[0020] 3. The sludge from the sewage treatment plant is the result of the treatment of organic wastewater, so that the sludge contains groups such as hydroxyl (-OH), carboxyl (-COOH) and amino (-NH2). These groups undergo cross-linking reactions with the polymer chains in the oil-based paint to form a three-dimensional network structure.

[0021] R-OH+R'-COOH→RO-CO-R'+H2O

[0022] R-NH2+R'-COOH→R-NH-CO-R'+H2O.

[0023] Furthermore, in step 2), the temperature of high temperature carbonization is 450-550°C, and the time of high temperature carbonization is 0.5-4h, preferably 1-2h. The high temperature carbonization process of the present invention decomposes organic matter in oily paint and organic matter in sludge to form porous carbon material and carbon skeleton. The protective effect of nitrogen is to prevent the material from being oxidized at high temperature and ensure the structural integrity of the carbon material.

[0024] Furthermore, in step 3), the concentration of the KOH aqueous solution is 1.5-2.5 mol / L, preferably 1.8-2 mol / L, and the solid-liquid ratio of the carbon material to the KOH aqueous solution is 1 g: 10-30 mL, preferably 1 g: 15-20 mL. Step 3) The carbon material and the KOH aqueous solution are heated and stirred to react at a temperature of 60°C ± 5°C, and the reaction time is 10-15 hours. The KOH aqueous solution is heated to react with the carbon material, and the generated potassium salt can penetrate into the micropores of the carbon material, further etching and expanding the pores to form more micropores and mesopores. The activated sample is calcined and activated at high temperature to further increase the specific surface area and pore structure of the carbon material.

[0025] Furthermore, in step 3), the calcination activation temperature is 800-950°C, preferably 850-900°C, and the calcination activation time is 0.5-1h. Sulfuric acid can remove impurities and residual potassium salts on the surface of the carbon material, while improving the surface chemical properties of the carbon material, attaching sulfonic acid groups to the surface of the activated carbon, further adjusting the pore size distribution, and improving the adsorption performance of the activated carbon.

[0026] Furthermore, in step 4), the concentration of the sulfuric acid solution is 1-2 mol / L, and the solid-liquid ratio of the activated sample to the sulfuric acid solution is 1 g:20-30 mL, preferably 1 g:25 mL.

[0027] Furthermore, in step 4), the heating temperature is 35-45° C., the stirring rate is 700-800 r / min, and the reaction time is 20-30 h.

[0028] The present invention also provides the use of the activated carbon in adsorbing and capturing CO2.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1) The present invention uses sludge and oily paint as raw materials to prepare activated carbon. The sludge contains abundant organic matter, which can be converted into carbon material in the subsequent carbonization process. In addition, the organic matter and mineral components in the sludge can form complex pore structures in the carbonization process. These pore structures help to improve the specific surface area and adsorption performance of the activated carbon. In particular, the trace elements and minerals in the sludge can enhance the surface activity of the activated carbon and improve its adsorption capacity for specific gases (such as carbon dioxide). The oily paint forms high molecular polymers during the free radical polymerization process. These polymers can enhance the mechanical strength of the sludge, which helps to maintain the structural integrity of the carbon material in the subsequent carbonization and activation process, and avoid disintegration or breakage during high temperature treatment.

[0031] 2) Sludge is a byproduct of sewage treatment and usually needs to be treated and disposed. The present invention uses it to prepare activated carbon, which not only solves the problem of sludge treatment, but also realizes the recycling of resources, with significant environmental and economic benefits.

[0032] 3) The use of oil-based paint as a raw material for preparing activated carbon in the present invention helps promote pore formation. The high molecular polymer in the oil-based paint can form a complex network structure during the carbonization process. These structures decompose at high temperatures to form porous carbon materials. The presence of oil-based paint helps to form a richer and more stable pore structure and increase the specific surface area of ​​the activated carbon. In addition, it is also beneficial to improve the surface chemical properties. Certain functional groups in the oil-based paint can remain on the surface of the carbon material during the carbonization and activation process. These functional groups can improve the surface chemical properties of the activated carbon and enhance its adsorption capacity for specific gases. For example, certain oxygen-containing functional groups can improve the adsorption performance of activated carbon for acidic gases.

[0033] 4) The present invention also uses KOH reaction activation and H2SO4 modification to prepare activated carbon. KOH activation helps to promote pore formation, increase specific surface area, adjust pore size distribution, and improve surface chemical properties. H2SO4 modification allows sulfonic acid groups to attach to the surface of activated carbon, which can improve the adsorption efficiency of CO2. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0035] The waste sludge in the embodiment of the present invention comes from a sewage treatment plant, and its main components are water, organic matter and ash. The water content of the waste sludge is 58.14%, and the rest is mainly organic matter and ash, and the organic matter content is 41.86% of the total content of organic matter and ash.

[0036] The oil-based paint is a UV paint with a polyester content of more than 50%, wherein the acrylic resin content is 83% to 99%, the tripropylene glycol diacrylate content is 1% to 9%, and the trimethylolpropane triacrylate content is 0% to 8%.

[0037] Example 1: Preparation of KOH-activated carbon

[0038] 1. Use the waste sludge from the sewage treatment plant as raw material, first dry it in an oven to constant weight, then crush it, and pass it through a 200-mesh sieve to obtain 200-mesh dry sludge. Evenly mix the 200-mesh dry sludge, oil-based paint and ethanol in a conical flask at a feeding ratio of 1g:2mL:2mL, then add azobisisobutyronitrile (AIBN) in an amount of 1% of the amount of oil-based paint, and stir the solution until the AIBN solid is completely dissolved;

[0039] 2. Introduce high-purity nitrogen into the conical flask for 10 minutes. After all the air in the conical flask is exhausted, seal the conical flask with aluminum foil to isolate the air;

[0040] 3. Place the conical flask in a 60°C electric constant temperature water bath for 24 hours to complete the free radical polymerization reaction, during which the adsorbent precursor is precipitated;

[0041] 4. After the reaction is completed, place the filtrate in a vacuum drying oven at 85°C for 24 hours to completely remove moisture and obtain oily paint sludge.

[0042] 5. Carbonize the oily paint sludge in a tube furnace at 500℃ for 60min, with a heating rate of 10℃·min -1 ; The process was carried out under the protection of 200mL / min high-purity N2. After the program was completed, the tube furnace was closed until the furnace temperature dropped to ambient temperature;

[0043] 6. The carbonized sample was treated with 2 mol·L -1 In the KOH solution, the solid-liquid mass ratio is 1:20, and the reaction is stirred at 60°C for 12 hours (sealed with a sealing film); the supernatant is removed and dried in a forced air drying oven at 105°C for 12 hours;

[0044] 7. Use high-purity nitrogen as the ambient gas to activate the sample in a quartz tube furnace at 10℃·min -1 The temperature was raised to 900℃ at a rate of 100℃ and maintained for 30min; after the program was completed, KOH-sludge activated carbon was produced.

[0045] Example 2: CO2 dynamic adsorption experiment

[0046] The experimental conditions for activated carbon adsorption of CO2 are: dilute CO2 with N2 to form a N2-CO2 mixed gas, when the flow rate of N2 is 90mL / min, the flow rate of CO2 is 10mL / min, and the concentration of CO2 in the mixed gas is 10%. When the flow rate of N2 is 60mL / min, the flow rate of CO2 is 40mL / min, and the concentration of CO2 in the mixed gas is 40%.

[0047] The N2-CO2 mixed gas with CO2 concentration of 10% and 40% was passed through the activated carbon adsorbent at a flow rate of 100 mL / min at room temperature. The adsorption experiment was performed with a single dosage of 0.4 g of the adsorbent. According to this experimental condition, when the KOH-sludge activated carbon of Example 1 was used for adsorption, the test results are shown in Table 1.

[0048] Table 1 Dynamic adsorption of CO2 at different concentrations by KOH-sludge activated carbon

[0049]

[0050] Example 3: Preparation of KOH-H2SO4 sludge activated carbon

[0051] 1. The KOH-sludge activated carbon in Example 1 is the activated sludge activated carbon. 10 g of the activated sludge activated carbon is put into a conical flask, immersed in 250 mL of sulfuric acid solution, sealed and placed in a digital display constant temperature stirring water bath, heated to 40 ° C, and stirred at a speed of 800 r / min for 24 h;

[0052] 2. Filter the activated carbon in the conical flask, place the filtrate in a 105°C forced air drying oven and dry it for 24 hours to completely remove moisture and obtain an H2SO4-modified activated carbon product.

[0053] When the concentration of the sulfuric acid solution in step 1 of Example 3 is 1 mol / L and 2 mol / L respectively, the activated carbon products finally obtained are marked as KOH-1H2SO4-sludge activated carbon and KOH-2H2SO4-sludge activated carbon respectively.

[0054] Example 4: CO2 dynamic adsorption experiment

[0055] The CO2 dynamic adsorption experiment was carried out using the KOH-1H2SO4-sludge activated carbon and KOH-2H2SO4-sludge activated carbon of Example 3, respectively. The experimental steps were repeated in Example 2. The test results are shown in Table 2.

[0056] Table 2 Dynamic adsorption of CO2 at different concentrations by activated carbon after adjustment with different sulfuric acid concentrations

[0057]

[0058]

[0059] Example 5: Preparation of sludge activated carbon

[0060] Example 5 The preparation steps of activated carbon from sewage sludge were repeated in Example 1, except that step 6 was omitted and 2 mol·L -1 The other conditions remained unchanged, and finally the sludge activated carbon was prepared.

[0061] Example 6: CO2 dynamic adsorption experiment

[0062] The CO2 dynamic adsorption experiment was carried out using the sludge activated carbon of Example 5. The experimental steps were repeated in Example 2. The test results are shown in Table 3.

[0063] Table 3 Dynamic adsorption of CO2 at different concentrations by activated carbon from sludge

[0064]

[0065] Example 7: Preparation of KOH-HNO3 sludge activated carbon

[0066] 1. The KOH-sludge activated carbon in Example 1 is the activated sludge activated carbon. 10 g of the activated sludge activated carbon is put into a conical flask, immersed in 250 mL of nitric acid solution, sealed and placed in a digital display constant temperature stirring water bath, heated to 40 ° C, and stirred at a speed of 800 r / min for 24 h;

[0067] 2. Filter the activated carbon in the conical flask, place the filtrate in a 105°C forced air drying oven and dry it for 24 hours to completely remove moisture and obtain an HNO3-modified activated carbon product.

[0068] In Example 7, when the concentrations of the nitric acid solution in step 1 were 1 mol / L and 2 mol / L, the activated carbon products finally obtained were labeled as KOH-1HNO3-sludge activated carbon and KOH-2HNO3-sludge activated carbon, respectively.

[0069] Example 8: CO2 dynamic adsorption experiment

[0070] The CO2 dynamic adsorption experiment was carried out using the KOH-1HNO3-sludge activated carbon and KOH-2HNO3-sludge activated carbon of Example 7, respectively. The experimental steps were repeated in Example 2. The test results are shown in Table 4.

[0071] Table 4 Dynamic adsorption of CO2 at different concentrations by activated carbon after adjustment with different nitric acid concentrations

[0072]

[0073] Example 9: Preparation of KOH-sawdust activated carbon

[0074] Example 9 The preparation steps of KOH-sawdust activated carbon are repeated in Example 1, with the only difference being that "in step 1, the 200-mesh dry sludge is replaced with 200-mesh dry sawdust of equal mass", and the other conditions remain unchanged, and finally KOH-sawdust activated carbon is obtained.

[0075] Example 10: CO2 dynamic adsorption experiment

[0076] The KOH-sawdust activated carbon of Example 9 was used to carry out a CO2 dynamic adsorption experiment. The experimental steps were repeated in Example 2. The test results are shown in Table 5.

[0077] Table 5 Dynamic adsorption of CO2 at different concentrations by KOH-sawdust activated carbon

[0078]

[0079] Example 11: Preparation of KOH-H2SO4 sawdust activated carbon

[0080] 1. Using the KOH-sawdust activated carbon of Example 9 as the activated sawdust activated carbon, take 10 g of the activated sawdust activated carbon and put it into a conical flask, immerse it in 250 mL of sulfuric acid solution, seal it and place it in a digital display constant temperature stirring water bath, heat it to 40°C, and stir it at a speed of 800 r / min for 24 hours;

[0081] 2. Filter the activated carbon in the conical flask, place the filtrate in a 105°C forced air drying oven and dry it for 24 hours to completely remove moisture and obtain H2SO4-modified sawdust activated carbon.

[0082] When the concentration of the sulfuric acid solution in step 1 of Example 11 is 1 mol / L and 2 mol / L respectively, the activated carbon products finally obtained are marked as KOH-1H2SO4-sawdust activated carbon and KOH-2H2SO4-sawdust activated carbon respectively.

[0083] Example 12: CO2 dynamic adsorption experiment

[0084] The CO2 dynamic adsorption experiments were carried out using the KOH-1H2SO4-sawdust activated carbon and the KOH-2H2SO4-sawdust activated carbon of Example 11. The experimental steps were repeated in Example 2. The test results are shown in Table 6.

[0085] Table 6 Dynamic adsorption of different concentrations of CO2 on sawdust activated carbon after adjustment of different sulfuric acid concentrations

[0086]

[0087] Example 13: Dynamic adsorption experiment of CO2 by conventional activated carbon

[0088] Conventional activated carbon (coconut shell, fruit shell) was used to conduct a CO2 dynamic adsorption experiment. The experimental steps were repeated in Example 2. The test results are shown in Table 7.

[0089] Table 7 Dynamic adsorption of CO2 at different concentrations by conventional activated carbon

[0090]

[0091] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.

Claims

1. An activated carbon for capturing carbon dioxide and its preparation method and application, characterized in that The following steps are involved: 1) The waste sludge from the sewage treatment plant is used as raw material, first dried in an oven to constant weight, then crushed and sieved to obtain sludge powder; then, under the protection of an inert atmosphere, the sludge powder, oily paint, and initiator azobisisobutyronitrile are heated and stirred in ethanol to carry out a free radical polymerization reaction, and solids are precipitated in the process, which are filtered and dried to obtain oily paint sludge; 2) Carbonizing the oily paint sludge at high temperature in a tubular furnace with N2 atmosphere to obtain carbon material; 3) The carbon material is immersed in a KOH aqueous solution and heated and stirred for reaction. After the reaction is completed, the carbon material is filtered and dried. The dried sample is then placed in a tubular furnace with a N2 atmosphere for calcination and activation; 4) immersing the sample activated in step 3) in a sulfuric acid solution, heating and stirring to react, and after the reaction is completed, filtering and drying to obtain the activated carbon product.

2. The activated carbon for capturing carbon dioxide and its preparation method and application as claimed in claim 1, characterized in that In step 1), the water content of the waste sludge is 55%-60%, and the rest is mainly organic matter and ash, and the organic matter content is 40%-50% of the total content of organic matter and ash; the oil-based paint is a UV paint with a polyester content of more than 50%.

3. The activated carbon for capturing carbon dioxide and its preparation method and use as claimed in claim 1, characterized in that In step 1), the solid-liquid ratio of sludge powder to oil-based paint is 1:1-3, preferably 1:1.5-2; the amount of azobisisobutyronitrile is 0.5-2% of the mass of the oil-based paint, preferably 0.8-1%; the volume ratio of the oil-based paint to ethanol is 1:0.5-2, preferably 1:0.8-1; Step 1) The temperature of the free radical polymerization reaction is 60°C ± 5°C and the reaction time is 20-30h.

4. The activated carbon for capturing carbon dioxide and its preparation method and application as claimed in claim 1, characterized in that In step 2), the high temperature carbonization temperature is 450-550° C., and the high temperature carbonization time is 0.5-4 h, preferably 1-2 h.

5. The activated carbon for capturing carbon dioxide and its preparation method and use as claimed in claim 1, characterized in that In step 3), the concentration of KOH aqueous solution is 1.5-2.5 mol / L, preferably 1.8-2 mol / L, the solid-liquid ratio of carbon material to KOH aqueous solution is 1 g:10-30 mL, preferably 1 g:15-20 mL; step 3) the carbon material and KOH aqueous solution are heated and stirred for reaction at 60°C±5°C, and the reaction time is 10-15 h.

6. The activated carbon for capturing carbon dioxide and its preparation method and use as claimed in claim 1, characterized in that In step 3), the temperature of calcination and activation is 800-950° C., preferably 850-900° C., and the time of calcination and activation is 0.5-1 h.

7. The activated carbon for capturing carbon dioxide and its preparation method and use as claimed in claim 1, characterized in that In step 4), the concentration of the sulfuric acid solution is 1-2 mol / L, and the solid-liquid ratio of the activated sample to the sulfuric acid solution is 1 g:20-30 mL, preferably 1 g:25 mL.

8. The activated carbon for capturing carbon dioxide and its preparation method and use as claimed in claim 1, characterized in that In step 4), the heating temperature is 35-45° C., the stirring rate is 700-800 r / min, and the reaction time is 20-30 h.

9. An activated carbon for capturing carbon dioxide prepared by the method according to any one of claims 1 to 8.

10. Use of the activated carbon as claimed in claim 9 in the adsorption and capture of CO2.